Numerical Investigation on the Performance of a Transonic Axial Compressor with Inlet Distortion and Low Reynolds Number - Zhiping Li; Xingyu Zhu; Zhaoqi Yan; Tianyu Pan (Energies, 2022)
The performance and stability of the transonic fan stage with a nonuniform inflow is a key issue in aero engine operation, and the coupling of inlet distortion and low Reynolds numbers at high altitude creates more severe challenges to aero engines. This work used computational methods to explore the performance and stability of a transonic fan stage with inlet distortion and a low Reynolds number. To investigate this issue, the transonic fan stage NASA stage 67 with a 180° total pressure distortion at a low Reynolds number was selected as the test case. Full-annulus 3D unsteady simulations were conducted to reveal the details of the flow field under coupling conditions. The computational results under different conditions were analyzed and showed that the coupling effect was not linearly stacked with single factors. The low Reynolds number in the coupling case thickened the boundary layer on the blade surface, and, on the one hand, the profile loss in the hub region increased. On the other hand, the structure of shock wave was converted in the tip region, which increased the shock loss significantly. In addition, the variation in the shock wave structure reconstructed the pressure distribution on the blade surface, allowing the fluid to migrate to the tip region, which affected the tip flow structure and ultimately delayed the stability boundary.